The Important Parts of International E-Commerce Business, Focusing on B2B - Ratrawetakorn, Teerat; Udomsap, Rapee; Aquino, Conrado (Business Administration and Management Journal Review, 2018)
The E-Commerce business, which is an integral part of the vast Internet system, has been expanding tremendously as a result of the non-stop rapid increase in the number of the world’s Internet users. This phenomenal expansion has directly caused the overall business structure to change from what is mainly an offline nature to largely an online business. Evidently, the present business scenario indicates what efficiency is, wherein both buyers and sellers can find each other quickly and effectively and carry out their transactions more conveniently. In Thailand, E-Commerce business predominates various entrepreneurial categories based on their different business purposes, e.g., fashion products, consumer goods, transportation and payment services, etc. Such reality prompted the country to adapt measures that can cope with the E-Commerce business effectively and at the same time supporting the large number of local Internet users. In the same manner, it is inevitable that domestic entrepreneurs must have a thorough understanding of international E-Commerce business to help improve national business and economy. E-Commerce also plays an important role in stimulating the economy as a whole because international trade is one of the vital driving force that helps Thailand strengthen its economic and social development efforts.